Velopharyngeal Structural and Muscle Variations in Children With 22q11.2 Deletion Syndrome: An Unsedated MRI Study. (October 2019) - Kollara, Lakshmi; Baylis, Adriane L.; Kirschner, Richard E.; Bates, D. Gregory; Smith, Mark; Fang, Xiangming; Perry, Jamie L.
Objective: The 22q11.2 deletion syndrome (22q11.2DS) is the most common genetic cause of velopharyngeal dysfunction; however, limited information exists regarding variations in velopharyngeal anatomy in this clinically challenging population. The purpose of this study was to examine velopharyngeal characteristics among young children with 22q11.2DS in comparison to a normative cohort using an innovative, nonsedated magnetic resonance imaging (MRI) scanning protocol. Methods: Fifteen children with 22q11.2DS and 15 age- and gender-matched controls with normal velopharyngeal anatomy (ages 4-12) successfully completed the MRI protocol. Eighteen velopharyngeal and 2 related craniofacial measures were examined. Analysis of covariance was used to compare differences between the experimental and the control groups. Results: The 22q11.2DS group demonstrated a significantly thinner velum ( P < .0005) and a larger pharyngeal depth ( P = .007) compared to the matched control group. Findings in the current study also demonstrated that the levator veli palatini muscle is significantly shorter ( P = .037) and thinner ( P = .025) in the 22q11.2DS cohort, with a significantly shorter origin-to-origin distance ( P < .0005) and a greater angle of origin ( P = .001) compared to healthy peers. Conclusion: Children with 22q11.2DS demonstrated multiple variations that may contribute to velopharyngeal dysfunction by altering the anatomic characteristics of the velopharyngeal port, the levator muscle, and associated structures. This investigation represents the first and largest attempt to characterize velopharyngeal anatomy in children with 22q11.2DS using a nonsedated MRI protocol.